2019
DOI: 10.1103/physrevresearch.1.033059
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of complex oxide films: Role of surface reconstructions

Abstract: Achieving atomically flat and stoichiometric films of complex multicomponent oxides is crucial to integrating these materials in both established and emerging technologies. While pulsed laser deposition (PLD) can in principle produce these high-quality films, growth experiments often result in unsatisfactory morphologies with rough surfaces and nonstoichiometric compositions. To understand the cause, the growth needs to be followed at an atomic level from its early stages as a function of the growth conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
(77 reference statements)
0
16
0
Order By: Relevance
“…Because of the lack of experimental input on the surface structures, processes occurring at the surfaces of multi-element oxides like LSMO are most oen modeled based on bulk terminations. 3 However, this is a crude oversimplication of reality: the many available surface science studies on binary oxides and pioneering studies on ternary oxides [47][48][49][50][51][52][53][54] have demonstrated that their surfaces rarely show a bulk termination. Instead, they tend to exhibit a variety of reconstructions with remarkable structural and electronic variability as a function of oxygen content and cation stoichiometry.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the lack of experimental input on the surface structures, processes occurring at the surfaces of multi-element oxides like LSMO are most oen modeled based on bulk terminations. 3 However, this is a crude oversimplication of reality: the many available surface science studies on binary oxides and pioneering studies on ternary oxides [47][48][49][50][51][52][53][54] have demonstrated that their surfaces rarely show a bulk termination. Instead, they tend to exhibit a variety of reconstructions with remarkable structural and electronic variability as a function of oxygen content and cation stoichiometry.…”
Section: Introductionmentioning
confidence: 99%
“…Migration of these charged V 2− Sr and Sr 2+ ad point defects is activated at temperatures as low as 200 • C. Moreover, when the surface is additionally enriched by Sr adatoms via evaporation, the adatoms are mobile at both terminations and start to aggregate at temperatures as low as 150 • C, as shown in the Supplemental Material (SM). The disappearance/appearance of O likely originates from the exchange with the subsurface region, because lateral diffusion across the whole micrometers-wide domains is unlikely [41,42]. The temperature range for migration of vacancies is slightly lower than reported in the literature for SrTiO 3 [43,44], but can be rationalized by the presence of electric fields related to the charged defects.…”
mentioning
confidence: 79%
“…This provides the basis to relate atomic-scale surface reconstruction to the surface composition, but also to reproducibly and reversibly adjust the surface structure on the same bulk material. This capability was used for devising a novel method to determine the cation flux in PLD with unprecedented precision [10], to understand the influence of surface structure on the evolving growth morphology [11], and to understand how the surface reconstructions control the incorporation of oxygen in model cathodes for solid oxide fuel cells [12].…”
Section: Combing Surface Science and Pulsed Laser Deposition: An Unusmentioning
confidence: 99%